The mathematical model of the menstrual cycle with time delay depending on the researched function - Grigolienė, Rasa; Pridotkas, Gintaras; Bučys, Kostas; Švitra, Donatas (Lietuvos matematikos rinkinys, 2001)
There is not abstarct.